2012
DOI: 10.1007/s10865-012-9421-5
|View full text |Cite
|
Sign up to set email alerts
|

Using novel methods to examine stress among HIV-positive African American men who have sex with men and women

Abstract: Biomarker composites (BCs) that objectively quantify psychosocial stress independent of self report could help to identify those at greatest risk for negative health outcomes and elucidate mechanisms of stress-related processes. Here, BCs are examined in the context of existing disease progression among HIV-positive African American men who have sex with men and women (MSMW) with high stress histories, including childhood sexual abuse. Participants (N = 99) collected 12-h overnight and morning urine samples fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…A total of 295 men were screened, and 117 met the eligibility criteria ( Figure 1); 99 had complete baseline data (the data for these men were used in an earlier baseline report on this population 40 ). Of these 99 men, 88 participated in either the ES-HIM or the HP condition (i.e., attended at least the first session).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 295 men were screened, and 117 met the eligibility criteria ( Figure 1); 99 had complete baseline data (the data for these men were used in an earlier baseline report on this population 40 ). Of these 99 men, 88 participated in either the ES-HIM or the HP condition (i.e., attended at least the first session).…”
Section: Methodsmentioning
confidence: 99%
“…A baseline analysis of a larger cohort from this same sample 40 showed that severe CSA and a greater number of PTSD symptoms were significantly associated with increased sexual risk behaviors. In addition, clinically meaningful PTSD symptom levels (PDS score above 17) predicted baseline biomarker composite scores.…”
Section: Childhood Sexual Abuse Severity and Psychological Symptomsmentioning
confidence: 95%
See 3 more Smart Citations